A complex case of a granulosa cell tumour. Issue 12 (17th December 2021) - Agius, Theresa; Gatt, Michaela; Falzon, Dylan; Babic, Darko
Abstract : This is a case of a 73-year-old woman who first presented in 2020 with a fullness in her abdomen. After several thorough investigations and unforeseen complications, the fullness was diagnosed as a granulosa cell tumour. In 2003, she had been diagnosed with a granulosa cell tumour of the ovary. Complete excision was performed, however she was not given a follow-up appointment after the procedure. This case highlights the importance of frequent follow-up of these tumours, the high recurrence rate, the severe complications which may result and the awareness of possible variations in this tumour's histologic appearance.